Strengthening The Literacy Culture Of Reading The Yellow Book At The Darus Salam Dringu Islamic Boarding School, Probolinggo District - Chomaidah, Siti; Prasetiya, Benny (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
This study discusses the strengthening of literacy culture in reading yellow books through the Sorogan method at the Darus Salam Dringu Islamic Boarding School, Probolinggo Regency. Yellow books as classical Islamic books have an important role in Islamic boarding school education. However, students' interest in literacy towards these books is still low. This study uses a qualitative approach with a case study method to identify effective strategies in strengthening literacy culture in Islamic boarding schools. The results of the study indicate that the Sorogan method, which involves direct interaction between students and teachers, is effective in improving students' understanding of yellow books. In addition, routine reading activities 15 minutes before learning, additional discussion sessions, and the provision of adequate library facilities also support increased literacy interest. However, this study also identifies challenges faced, such as limited access to technology and variations in students' abilities in understanding yellow books. The results of this study indicate that the Darus Salam Dringu Islamic Boarding School has succeeded in implementing several significant literacy strengthening strategies, although further efforts are still needed to overcome existing obstacles. Overall, this study offers a new perspective on the implementation of yellow book literacy in Islamic boarding schools, showing that innovative learning strategies and strengthening facilities can support the development of intellectual abilities and character of students in accordance with Islamic teachings.